Diagnosis and treatment of small intestinal bacterial overgrowth - Zadrozna, Karolina; Wysokińska, Olga; Małek, Anna; Iwaniszyn-Zapołoch, Klara; Wójcik, Bartłomiej; Fabiś, Mateusz; Żyga, Justyna (Journal of Education, Health and Sport, 2022)
Introduction: The human digestive tract contains 38 trillion bacteria in the colon. Physiologically, there is much less of them in other parts of digestive tract. The concentration of bacterial colonies grows along the intestine. Small intestinal bacterial overgrowth (SIBO) is characterized by an increased number of bacteria in the small intestine that correlates with gastrointestinal symptoms. The main symptoms of SIBO are bdominal bloating and diarrhea. Diagnostic methods used in SIBO include measuring methane or hydrogen levels. However, the use of antibiotics is prevalent, there is still a necessity to search for the gold standard of treatment. Objective: The purpose of this paper is to review the current knowledge on the management of patients with proliferative small intestinal bacterial flora syndrome. Particular attention was paid to the types of diagnosis and treatment of this ailment in recent years. Material and methods: The review includes publications published in 2001- 2022. Data were collected using PubMed or az published online American College of Gastroenterology (ACG) 2020 guidelines. Results: SIBO is an incompletely understood disease. Its symptoms are nonspecific and found in many gastrointestinal disorders, and its diagnosis is not fully specified. The gold standard for diagnosis is the collection of a small bowel aspirate during endoscopic examination. Antibacterial treatment is given empirically, mainly rifaximin, while other types of treatment are not strongly established in the publications. Conclusions: The lack of standardized management and the lack of sufficient evidence for the effectiveness of current methods make SIBO a recurrent complaint. All above aspects confirm that SIBO requires a lot of research to provide better life quality for these patients.